FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU HIJAU PADA PROGRAM RECYCLE POINT LE MINERALE DI DAERAH ISTIMEWA YOGYAKARTA: FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU HIJAU PADA PROGRAM RECYCLE POINT LE MINERALE DI DAERAH ISTIMEWA YOGYAKARTA - Guruh Ghifar Zalzalah; Elvina Anggraini; Adhi Prakosa; Pradita Nindya Aryandha; Fikri Farhan (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
The increasing volume of waste is a challenge for environmental sustainability and public health. Le Minerale's recycling point program offers a solution by providing recycling facilities and increasing awareness of waste management. This initiative reduces waste in landfills and builds responsibility in maintaining a clean environment. This research aims to determine the influence of sustainable social development goals, environmentally friendly sustainable development goals, attitudes, intentions on green behavior on the Le Minerale recycle point program in Yogyakarta. This research was conducted in the Yogyakarta Special Region in 2024, the sample used was 124 respondents. The sampling technique uses a purposive sampling method. The data analysis technique in this research uses partial least squares structural equation modeling (SEM-PLS) using the WarpPLS version 7.0 application. The results of the research show that social sustainable development goals, environmentally friendly sustainable development goals, attitudes have a significant positive effect on intentions and intentions have a significant positive effect on green behavior.